Insomnia in Obsessive-Compulsive Disorder: Clinical Presentation and Management: A Narrative Review - Choten Gyaltshen; Manisankar Bala; Devdulal Roy (Journal of Sleep Medicine, 2026)
Insomnia causes substantial distress in patients with obsessive-compulsive disorder (OCD), worsens symptom severity, and reduces overall quality of life. Recent studies have highlighted a complex association between insomnia and OCD, suggesting a possible bidirectional relationship mediated by depression, anxiety, and stress. Insomnia symptoms are not merely features of psychopathology but may also share neurophysiological links with OCD. Recent evidence has clarified possible epigenetic and neuropsychological mechanisms underlying insomnia symptoms in OCD. Although insomnia symptoms have limited diagnostic value in OCD, their effects on phenomenology, symptom severity, and treatment outcomes are clinically relevant. Insomnia symptoms are recognized as negative contributors to OCD treatment outcomes, yet they are rarely assessed or treated. Concurrent treatment of insomnia symptoms is recommended to improve OCD symptoms and treatment outcomes. Effective management typically combines non-pharmacological and pharmacological interventions tailored to each patient’s needs. This review examines current evidence and approaches to treating insomnia in patients with OCD.